2013
DOI: 10.5194/acp-13-6023-2013
|View full text |Cite
|
Sign up to set email alerts
|

Airborne lidar measurements of surface ozone depletion over Arctic sea ice

Abstract: A differential absorption lidar (DIAL) for measurement of atmospheric ozone concentration was operated aboard the Polar 5 research aircraft in order to study the depletion of ozone over Arctic sea ice. The lidar measurements during a flight over the sea ice north of Barrow, Alaska, on 3 April 2011 found a surface boundary layer depletion of ozone over a range of 300 km. The photochemical destruction of surface level ozone was strongest at the most northern point of the flight, and steadily decreased towards la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The ground based Differential Absorption Lidar (DIAL) instrument used for this study had a design that was essentially equivalent to the system employed for previous ship and aircraft based studies of ozone over sea ice [1,2]. A schematic diagram of the lidar is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ground based Differential Absorption Lidar (DIAL) instrument used for this study had a design that was essentially equivalent to the system employed for previous ship and aircraft based studies of ozone over sea ice [1,2]. A schematic diagram of the lidar is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ozone depletion has been explained as being caused by Bromine atoms that originate from photochemical reactions on snow and fresh sea ice surfaces [6]. The aircraft and ship based lidar measurements over the sea ice have found that the ODEs extend from the surface to heights of a few hundred meters [1,2]. Analyses of air trajectories revealed that ozone depleted air spent significant time in the surface layer over the frozen ocean surface and open leads [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lidar system for tropospheric ozone and aerosol measurements was developed at York University for installation on aircraft [1,2]. This was installed on a Twin Otter aircraft in August 2013 for participation in a field campaign that was designed to study the air pollution from the oil sands extraction activities north of Fort McMurray, Alberta.…”
Section: Introductionmentioning
confidence: 99%